Treatment of Symptom Clusters in Schizophrenia, Bipolar Disorder and Major Depressive Disorder With the Dopamine D3/D2 Preferring Partial Agonist Cariprazine - Batinic, Borjanka; Ristic, Ivan; Zugic, Milica; Baldwin, David S. (Frontiers in Psychiatry, 2021)
Cariprazine is currently approved for the treatment of patients with schizophrenia (USA and EU), and for manic, depressive, and episodes with mixed features in bipolar I disorder (USA): several randomized controlled studies have also explored its efficacy in patients with major depressive disorder. This review summarizes its current therapeutic uses and potential advantages for treating the main symptoms of schizophrenia, bipolar I and major depressive disorder, considering its pharmacodynamic properties, efficacy, and tolerability. Its predominantly D3 receptor preferring affinity, with functional selectivity according to the prevailing neuronal environment, contributes to its efficacy across a wide array of psychopathological symptoms (including reality distortion, disorganized thought, negative symptoms, mood disturbance, anhedonia, and cognitive impairment), and to a favorable side effect profile. Cariprazine may be a “drug of choice” in patients with predominant negative and cognitive symptoms of schizophrenia, as well as those with metabolic syndrome. Further investigation of its relative efficacy when compared to aripiprazole or other active comparators is warranted. Its effectiveness in the treatment of bipolar mania, bipolar I depression and bipolar I episodes with mixed features, with minimal accompanying metabolic changes is well-established. The longer half-life and delayed time to relapse in patients diagnosed with schizophrenia when compared to other second-generation antipsychotics represent other advantages, given the high rates of non-adherence and frequent relapses seen in clinical practice. Its efficacy in overlapping symptom domains in other major psychiatric disorders appears promising.